REPRESENTASI IBU BEKERJA VS IBU RUMAH TANGGA DI MEDIA ONLINE: Analisis Wacana pada Situs Kompasiana.Com - Putri Limilia; Ditha Prasanti (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The aim of the study is to identify how women makes discourse about working mom vs fulltime mothers in online media particularly Kompasiana. It is also to determine at the discourse of working mothers versus house wife which raised by women in a virtual world based on the experience of being a mother. This research applied Theo Van Leeuwen discourse analysis which reviewed the text from the perspective of how a social actor enclosure or inclosure from a text or news. It reveals that there are some strategies used by the media or the author in generating or eliminating social actors from a text. The result also showed that women was make discourse about working mom vs fulltime mothers through a series of narratives about the advantages and disadvantages of each profession (working mother and fulltime mothers). Discourse raised by the authors who are working mother (mother works from outside the home or mothers working from home). Most authors make discourse about how fellow mothers should not blame the decisions they make in choosing a profession.